17th International Conference on Textures of Materials (ICOTOM 17). Issue 1 (24th April 2015) - Skrotzki, Werner; Oertel, Carl-Georg
Abstract : The 17th International Conference on Textures of Materials (ICOTOM 17) took place in Dresden, Germany, August 24-29, 2014. It belongs to the "triennial" series of ICOTOM meetings with a long tradition, starting in 1969 - Clausthal, 1971 - Cracow, 1973 - Pont-à-Mousson, 1975 - Cambridge, 1978 - Aachen, 1981 - Tokyo, 1984 - Noordwijkerhout, 1987 - Santa Fe, 1990 - Avignon, 1993 - Clausthal, 1996 - Xian, 1999 - Montreal, 2002 - Seoul, 2005 - Leuven, 2008 - Pittsburgh, 2011 - Mumbai, 2014 - Dresden. ICOTOM 17 was hosted by the Dresden University of Technology, Institute of Structural Physics. Following the tradition of the ICOTOM conferences, the main focus of ICOTOM-17 was to promote and strengthen the fundamental understanding of the basic processes that govern the formation of texture and its relation to the properties of polycrystalline materials. Nonetheless, it was the aim to forge links between basic research on model materials and applied research on engineering materials of technical importance. Thus, ICOTOM 17 provided a forum for the presentation and discussion of recent progress in research of texture and related anisotropy of mechanical and functional properties of all kinds of polycrystalline materials including natural materials like rocks. Particular attention was paid to recent advances in texture measurement and analysis as well as modeling of texture development for all kinds of processes like solidification, plastic deformation, recrystallization and grain growth, phase transformations, thin film deposition, etc. Hence, ICOTOM 17 was of great interest to materials scientists, engineers from many different areas and geoscientists. The topics covered by ICOTOM 17 were: 1. Mathematical, numerical and statistical methods of texture analysis 2. Deformation textures 3. Crystallization, recrystallization and growth textures 4. Transformation textures 5. Textures in functional materials 6. Textures in advanced materials 7. Textures in rocks 8. Texture related research on microstructures 9. Texture-induced anisotropy 10. Insight through new experimental methods 11. Technological applications of texture studies 12. Other new developments and future trends related to the field While there was large interest in the topics 2, 3 and 8, contributions to topic 7 were much less than expected. ICOTOM 17 attracted 266 scientists from 34 countries with about one third of the participants being students. This is a very good ratio showing that we could attract the young generation. There have been 216 oral and 76 poster presentations, three of which received a poster award. It is our pleasure to thank the members of the International ICOTOM Committee for their valuable help, especially for proposing and choosing the 15 plenary speakers as well as the distinguished scientist of the texture community for the "Bunge Award". 130 papers were submitted for publication in the proceedings, 116 were accepted after reviewing. We would like to express our thanks to all referees for their efficient and prompt efforts. We acknowledge particularly support from the German Research Society (DFG) and the City of Dresden. We are also grateful for industrial support from Bruker Nano GmbH, Oxford Instruments GmbH, Ametek GmbH / EDAX, Labosoft S.C., PANalytical GmbH and IOP Publishing. Finally we thank all members of the National Organizing Committee, Intercom Dresden and Conwerk / Laboratory Ten for the excellent organization of ICOTOM 17 and the very pleasant collaboration. On the first day of the conference three tutorials have been offered. Each of them has been attended by about 30 participants. 1. Texture-aided residual stress identification system (TARSIuS) (organized by Prof. Dr. J. Bonarski and Mr. B. Kania) 2. MTEX - MATLAB toolbox for quantitative texture analysis (organized by Dr. R. Hielscher and Mr. F. Bachmann) 3. Grain boundary engineering (organized by Prof. N. Bozzolo and Prof. Dr. A.D. Rollett) A highlight of ICOTOM 17 was the ceremony honoring Prof. Dr. Claude Esling with the Bunge Award for his distinguished contributions to the field of Textures of Materials and his continuous effort to pass on his knowledge to future generations of texture experts. The Bunge Award is named after Professor Hans Bunge († 2004), to whom the world's texture community is very much indebted not only for his magisterial work on the Mathematical Theory of Texture, but also for his lifelong promotion of the field of Textures of Materials. To the great delight of all participants, Helga Bunge and her son Prof. Hans-Peter Bunge, to whom many of the older generation have a personal relationship, attended the ceremony (see Fig. 1 in the PDF). Following the award ceremony Prof. Dr. Claude Esling gave an in memoriam tribute to Prof. Dr. Richard Penelle, who was an internationally recognized texture specialist. Details can be found in the proceedings paper by Esling et al. [this issue]. During the conference the International ICSMA Committee decided to convene the next conference in St. George, USA, in 2017. We wish the organizers of ICOTOM 18 great success and look forward to meeting you in St. George. Werner Skrotzki* (Chairman of ICOTOM 17, Dresden University of Technology) Carl-Georg Oertel (Dresden University of Technology) Guest Editors Dresden, March, 2015 (* Corresponding author; e-mail address: werner.skrotzki@tu-dresden.de)